Electromagnetic Field Generated by an Earthquake Source Due to Motional Induction in 3D Stratified Media, and Application to 2008 Mw 6.1 Qingchuan Earthquake. Issue 10 (24th October 2021) - Zhao, Jie; Gao, Yongxin; Tang, Ji; Klemperer, Simon L.; Wen, Jian; Chen, Chieh‐Hung; Chong, Jiajun
Abstract: Movement of the conductive subsurface medium in the Earth's magnetic field can generate electromagnetic (EM) disturbances. This phenomenon is referred to as the motional induction (MI) effect and, though previously proposed as a possible mechanism for the generation of earthquake‐associated EM signals, has not yet been well understood. In this study, we present a semianalytical method to derive the EM response to an earthquake due to the MI effect in a 3D horizontally layered model. We solve the coupled elastodynamic and Maxwell's equations in the frequency–wavenumber domain through the global matrix method and then compute the seismic and EM responses in the time domain. We first verify the proposed method by comparing results to the analytical solution in a full‐space model and then conduct numerical simulations to investigate the properties of the EM fields and their sensitivities to the rock conductivity. Finally, we use the proposed method to model coseismic EM data observed during the 2008 M w 6.1 Qingchuan earthquake. The results show that the simulated coseismic electric fields can fit the observed electric signals well in both arrival time and amplitude, suggesting that the MI effect is a possible mechanism for the generation of the observed electric signals. The simulated magnetic fields are 1 order of magnitude weaker in amplitude than the observed magnetic data, implying that the observed magnetic fields are mainly generated by other mechanisms. Plain Language Summary: Much observational evidence shows that anomalous electromagnetic (EM) signals are detected during earthquakes. These EM signals have attracted a lot of attention because they might be useful for earthquake early warning and disaster mitigation. But we lack sufficient understanding. Although the motional induction (MI) effect has been proposed, the precise mechanism by which earthquake (rupture) energy transforms to EM energy is unclear. MI effect results from motion of the conductive subsurface medium in the ambient geomagnetic field due to the Faraday's law. In this study, we present a method to simulate the EM fields generated by the earthquake due to MI effect. Our results show that earthquakes can produce two kinds of EM signals. One arrives before the seismic waves (called early EM signals) and the other arrives simultaneously with seismic waves (called coseismic EM signals). We also use our method to simulate the EM data recorded during a real earthquake (which happened in 2008 in Sichuan, China). The synthetic coseismic electric fields can explain the observed data well, indicating that MI effect is an effective mechanism to produce the earthquake‐associated EM signals. Key Points: We present a method to simulate electromagnetic field generated by an earthquake due to motional induction effect in 3D‐layered media Numerical simulations are conducted to investigate the character of the electromagnetic fields and their sensitivity to rock conductivity The method is applied to the 2008 Qingchuan M w 6.1 earthquake; synthetic electric signals can explain observed electric signals